Recent Developments and Applications of Chiral Tetraphenylenes - Han, Jian-Wei; Chen, Jing-Xing; Li, Xin; Peng, Xiao-Shui; Wong, Henry N. C. (Synlett, 2013)
Developments of tetraphenylene chemistry in our laboratories (Shanghai and Hong Kong) since 2009 are summarized. The properties and new applications of the structurally unique tetraphenylene derivatives are described in the context of helical macrocycles, asymmetric catalysis, host–guest chemistry, and liquid crystalline molecules. Some future challenges in this field are also presented.1 Introduction2 Structure and Properties of Tetraphenylenes3 Tetraphenylenes and Helical Macrocycles4 Tetraphenylenes and Asymmetric Catalysis5 Tetraphenylenes and Host–Guest Chemistry6 Tetraphenylenes and Liquid Crystalline Molecules7 Conclusion and Perspectives
Keywords: tetraphenylene; asymmetric catalysis; helical structures; host–guest systems; liquid crystalline compounds